Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1210/endo.139.3.5768
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of PDX-1 Structure, Function, and Expression in Zebrafish*

Abstract: Development of the mammalian pancreas has been studied extensively in mice. The stages from budding of the pancreatic anlaga through endocrine and exocrine cell differentiation and islet formation have been described in detail. Recently, the homeodomain transcription factor PDX-1 has been identified as an important factor in the proliferation and differentiation of the pancreatic buds to form a mature pancreas. To evaluate the possibility of using zebrafish as a model for the genetic analysis of pancreas devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(36 citation statements)
references
References 36 publications
0
35
1
Order By: Relevance
“…By contrast, the ventral region does not express any endocrine markers at early stages, and is thought to give rise primarily to exocrine tissue (Kelly and Melton 2000). Both Xenopus pancreatic primordia express XLHbox8/Pdx1 (Offield et al 1996), a transcription factor that is similarly expressed in the pancreatic primordia of all vertebrates examined (Kim et al 1997a, b;Milewski et al 1998;Ohlsson et al 1993;Stoffers et al 1997), and which has been shown to be required for pancreas development in mouse and zebrafish (Ahlgren et al 1998;Yee et al 2001). We investigated expression of both Insulin and Pdx1 in stage 39 (Nieuwkoop and Faber 1994) tadpoles, where RA signaling had been blocked either by incubation with BMS493, or by microinjection of dominant-negative RARα2 (DN-RAR).…”
Section: Microinjection Of Mrna Into Xenopus Embryosmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, the ventral region does not express any endocrine markers at early stages, and is thought to give rise primarily to exocrine tissue (Kelly and Melton 2000). Both Xenopus pancreatic primordia express XLHbox8/Pdx1 (Offield et al 1996), a transcription factor that is similarly expressed in the pancreatic primordia of all vertebrates examined (Kim et al 1997a, b;Milewski et al 1998;Ohlsson et al 1993;Stoffers et al 1997), and which has been shown to be required for pancreas development in mouse and zebrafish (Ahlgren et al 1998;Yee et al 2001). We investigated expression of both Insulin and Pdx1 in stage 39 (Nieuwkoop and Faber 1994) tadpoles, where RA signaling had been blocked either by incubation with BMS493, or by microinjection of dominant-negative RARα2 (DN-RAR).…”
Section: Microinjection Of Mrna Into Xenopus Embryosmentioning
confidence: 99%
“…For example, the developing zebrafish pancreatic primordium expresses many of the same developmental control genes as the chick or mouse pancreas. These include the earliest molecular marker for the pancreas, pdx1 (Argenton et al 1999;Milewski et al 1998), and the endocrine cell markers islet1 (Ericson et al 1992) and pax6 (Biemar et al 2001). However, one apparent difference between amniote and zebrafish pancreas development has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it will be interesting to understand pancreas organogenesis in zebrafish not only from a standpoint of developmental biology but also from a comparative evolutionary perspective that may help to understand emergence of cellular interactions between these lineages. The combination of these factors makes the zebrafish an important experimental model for studying pancreas development [6,[9][10][11][12][13][14][15][16]. In particular, mutant analyses in the zebrafish provided insights into a developmental role of Hedgehog signaling during formation and differentiation of the endocrine pancreas [14,17,18], while its role during the exocrine pancreas development remains much less understood since only a limited developmental analyses of exocrine pancreas formation have been described until now [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Whole-mount in situ hybridization was performed on zebrafish embryos as described (Thisse and Thisse, 2008) using riboprobes for spaw (Ahmad et al, 2004), lefty1 (Bisgrove et al, 1999), lefty2 (Bisgrove et al, 1999), cmlc2 (Yelon et al, 1999), fkd2 (Odenthal and Nusslein-Volhard, 1998), ins (Milewski et al, 1998), gsc (Schulte-Merker et al, 1994, and ntl (Schulte-Merker et al, 1994).…”
Section: X-gal Staining and In Situ Hybridizationmentioning
confidence: 99%